An Examination of the MMPI-2 and MMPI-2-RF Validity Scales in Detecting Malingering and Dissimulation of Psychopathology - Patašius, Mantas; Laurinavičius, Alfredas (Psichologija, 2023)
This article examined the responsiveness of the MMPI-2 and MMPI-2-RF validity scales to simulation and dissimulation of psychopathology. Two experiments were performed. The simulation study included 66 participants (33 in the control group and 33 in the experimental group, age M = 36.76, SD = 15.24) and the dissimulation study included 60 patients diagnosed with a mental disorder (30 in the control group and 30 in the experimental group, M = 40.32, SD = 15.79). In both experiments, all participants completed the MMPI-2 questionnaire. Participants in the control group were given standard instructions, while participants in the experimental groups received instructions to either simulate symptoms of mental disorders or present themselves as completely healthy. Differences in the expected direction of the MMPI-2 psychopathology scales between the experimental and control groups indicated that the study instruction had an effect on the responses of the study participants. The results of the comparison of the validity scales showed that the majority of the MMPI-2 and MMPI-2-RF scales respond to an attempt to provide false information about oneself. Estimates of validity scales were statistically significantly different between control and experimental groups in both simulation and dissimulation studies, and the difference effect was mostly large. The obtained results show that the MMPI-2 and MMPI-2-RF are able to successfully recognize the simulation and dissimulation of psychopathology, which can be of practical value to specialists who seek to differentiate subjects who answer honestly from those who are feigning during psychological assessment.